2020
DOI: 10.1002/star.201900169
|View full text |Cite
|
Sign up to set email alerts
|

Rye Flour and Cellulose Reinforced Starch Biocomposite: A Green Approach to Improve Water Vapor Permeability and Mechanical Properties

Abstract: Research on starch-based biopolymers has increased because of their potential as environmentally friendly biodegradable substitutes to typical plastics. This study investigates the effect of rye flour as a main reinforcement agent as well as cellulose and citric acid in biocomposite starches on improving their water vapor permeability (WPF) and mechanical properties. The optimum point of the starch biocomposites obtained by Design of Experiments software 7.1.5 is run with 10% cellulose,and 10% rye flour with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…However, biodegradable packaging based on starch and other biopolymers, such as chitosan or gelatin, are susceptible to hydration and thus do not resist high relative humidity conditions, direct contact with liquid water, or foods with high moisture content [ 6 , 7 , 8 ]. Therefore, through previous research, mixtures of starch with other biopolymers have been developed with better barrier properties against moisture [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, biodegradable packaging based on starch and other biopolymers, such as chitosan or gelatin, are susceptible to hydration and thus do not resist high relative humidity conditions, direct contact with liquid water, or foods with high moisture content [ 6 , 7 , 8 ]. Therefore, through previous research, mixtures of starch with other biopolymers have been developed with better barrier properties against moisture [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…7), while others reported WVP of 2.35E-007 g s −1 m −1 Pa −1 for starch film containing 15% carboxy methyl cellulose. [6] Another research of us [16] showed 10% cellulose in starch biocomposite containing rye flour was optimum point for low WVP.…”
Section: Resultsmentioning
confidence: 98%
“…The optimization point of cellulose and glycerol and sorbitol contents for starch sheet with the best characterization was obtained using Design-Expert 7.1.5 software by D-Optimal procedure. In this way, three independent variables including cellulose (0-20%), glycerol (10-20%), and sorbitol (10-20%) were applied based on the previous experiment [16] and similar research. Mean differences between predicted and actual value of optimum point for validation were determined using one-way analysis of variance (ANOVA) and t-test.…”
Section: Optimization and Statistical Methodsmentioning
confidence: 99%
See 2 more Smart Citations